Patterning of lithium lanthanum titanium oxide films by soft lithography as electrolyte for all-solid-state Li-ion batteries - Kokal, I.; Göbel, O.F.; van den Ham, E.J.; ten Elshof, J.E.; Notten, P.H.L; Hintzen, H.T. (Ceramics international, 2015)
The combination of sol–gel processing and soft-lithographic patterning presents a promising route towards three-dimensional (3D) micro Li-ion electrodes, and may offer a viable approach for the fabrication of all-solid-state 3D Li-ion batteries. The methods are relatively simple and therefore cheap and moreover easy to scale up. In this paper, micro-patterned films of the Li-ion conducting perovskite-type phase with nominal composition Li0.29La0.57TiO3 (LLT) were prepared on silicon, using sol-gel synthesis in combination with micro-molding. After thermal annealing at 700°C, the phase formation, morphology, chemical composition and LLT film thickness were investigated by X-ray Diffraction (XRD), Scanning Electron Microscopy (SEM), Energy Dispersive Analysis of X-rays (EDAX) and Atomic Force Microscopy (AFM). The ionic conductivity of the LLT powder prepared during this study, determined by impedance spectroscopy, was 2.68·10−6S/cm at 25°C.